Liquid Waste Management Techniques by Using Equipment Operation System and Ipal System in PT Pertamina Trans Continental Dumai, Riau - Wulandari, Aprilia; Shandy, Jacinda Qoidatun (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Managing liquid waste from the oil and gas industry is crucial to prevent water pollution. PT Pertamina Trans Kontinental Dumai is one of the companies active in oil and gas operations, which produces liquid waste from exploration and production processes. This study aims to determine the company's fluid waste management system and the readiness of oil spill response equipment. The methods include direct observation, interviews with relevant parties, and literature review. The observations indicate that wastewater treatment is carried out through three stages: physical separation, chemical treatment, and biological processes using aerated tanks and sedimentation. The quality test results show that parameters such as BOD, COD, oil and grease, ammonia, total phenol, pH, and temperature are within the established quality standards. Additionally, PT Pertamina Trans Kontinental Dumai has complete and well-maintained emergency response facilities for oil spills, including oil booms, oil skimmers, dispersants, and sorbents. In conclusion, the management of liquid waste and equipment readiness for oil spill response at PT Pertamina Trans Kontinental Dumai complies with standards, thereby minimizing the risk of marine environmental pollution.